1977
DOI: 10.1080/00207597708247392
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Psychology in the African Context

Abstract: Clinical psychology arrived late on the African continent, and is still fighting for recognition. This state of affairs coupled with shortage of personnel has resulted in paucity of research data and poor quality of research work. These facts are documented with a brief historical and literature survey. The author observes that most of the available work is descriptive and anecdotal, based, as it were, on intuition rather than systematic observation. Selected works on schizophrenia, depression, anxiety, childr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1980
1980
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Ngissah (1977) compared a random sample of 500 people in Sacramento, California with 500 residents of Accra, Ghana and found that the African sample was significantly more negative towards mental illness. Boroffka and Olatawara (1977) reported that relatives of people with mental health problems within the Yoruba people in Nigeria try to conceal the illness from others, and Awaritefe (1977) found that Nigerian medical and nursing students expressed negative attitudes towards mental illness. However, the degree of stigma experienced by a person with mental health problems in an African context is often influenced by whether the person is blamed for having the illness.…”
Section: Attitudes and Response To Mental Illness In Africamentioning
confidence: 99%
“…Ngissah (1977) compared a random sample of 500 people in Sacramento, California with 500 residents of Accra, Ghana and found that the African sample was significantly more negative towards mental illness. Boroffka and Olatawara (1977) reported that relatives of people with mental health problems within the Yoruba people in Nigeria try to conceal the illness from others, and Awaritefe (1977) found that Nigerian medical and nursing students expressed negative attitudes towards mental illness. However, the degree of stigma experienced by a person with mental health problems in an African context is often influenced by whether the person is blamed for having the illness.…”
Section: Attitudes and Response To Mental Illness In Africamentioning
confidence: 99%
“…[36]. Adequate psychometric properties have been found with BDI-2 in several studies with Nigerian samples [37,38]. As evidence of convergent validity, BDII was positively correlated with Sub scale of Depression in MMPI-2 with r=0.60 [36].…”
Section: Introductionmentioning
confidence: 99%
“…Although, as various European (Wober 1975;Draguns 1977) and African (Abdi 1975;Awaritefe 1977) reviewers have noted, many of the methodological and conceptual problems that were so widespread two decades ago have remained, there have been a great many positive developments since that time. TransculturaUy sophisticated European psychiatrists have done research in African settings, anthropologists from various European countries have increasingly turned their attention to traditional healing in Africa, and more and more African psychiatrists, psychologists and social scientists have made significant research contributions.…”
mentioning
confidence: 99%